Microstructural Evolution During Deformation of a QP980 Steel - Salehiyan, Diyar; Samei, Javad; Amirkhiz, Babak Shalchi; Hector, Louis G.; Wilkinson, David S. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2020)
Quench and partitioning steels offer a valuable combination of high strength and ductility. Here we report on microstructural evolution in a QP980 steel during deformation. This is measured using a range of techniques including in-situ tensile tests coupled with scanning electron microscopy, ex-situ interrupted tensile tests coupled with electron back scattered diffraction, and X-ray diffraction measurements. Microstrain partitioning among ferrite, martensite, and retained austenite is quantified using microscopic digital image correlation. The average true strain in ferrite is approximately two and three times that in martensite and blocky retained austenite, respectively, consistent with nanohardness measurements of each phase. The combination of high strength and ductility of this steel is attributed to co-deformation of ferrite and tempered martensite. Some of the retained austenite blocks located at ferrite and martensite interfaces are almost fully transformed to martensite through transformation-induced plasticity, also contributing to ductility. Cracking of large blocky retained austenite in regions with more intense strain localization starts at relatively lower global strains. However, this appears to have little impact on the final failure process. Rather, it is the formation of large cavities in regions with higher martensite volume fraction that provides the primary mechanism of damage and failure.